Feelings of Contrast at Test Reduce False Memory in the Deese/Roediger-McDermott Paradigm - Cadavid, Sara; Beato, Maria Soledad; Suarez, Mar; Albuquerque, Pedro B. (Frontiers in Psychology, 2021)
False memories in the Deese/Roediger-McDermott (DRM) paradigm are usually explained in terms of the interplay between error-inflating (e.g., backward associative strength or BAS) and error-editing (e.g., monitoring) mechanisms. In this study, we focused on disqualifying monitoring, a decision process that helps participants to reject false memories through the recollection of collateral information (i.e., recall-to-reject strategies). Participants engage in recall-to-reject strategies using one of two metacognitive processes: 1) applying the logic of mutual exclusivity or (2) experiencing feelings of contrast between studied items and unstudied critical lures. We aimed to provide, for the first time in the DRM literature, evidence in favor of the existence of a recall-to-reject strategy based on the experience of feelings of contrast. One hundred forty participants studied six-word DRM lists (e.g., spy, hell, fist, fight, abduction, mortal), simultaneously associated with three critical lures (e.g., WAR, BAD, FEAR). Lists had extremely low or high levels of BAS. At the recognition test, participants were presented with either one or the three critical lures of the lists. Participants in the three-critical-lure condition were expected to increase their recall-to-reject strategies, as they would experience stronger feelings of contrast than the participants in the one-critical-lure condition. The results supported our hypothesis, with lower false recognition in the three-critical-lure condition than in the one-critical-lure condition. The extremely low BAS levels helped participants reduce false memory in the three-critical-lure condition. These findings suggest that, in the DRM context, disqualifying monitoring could be guided by experiencing feelings of contrast between different types of words.